If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + 5 = y Reorder the terms: 5 + 8x = y Solving 5 + 8x = y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 8x = -5 + y Combine like terms: 5 + -5 = 0 0 + 8x = -5 + y 8x = -5 + y Divide each side by '8'. x = -0.625 + 0.125y Simplifying x = -0.625 + 0.125y
| 3cos(2X)-2sin(2x)=(a)sin(bx+c) | | (2x+5)5= | | 2f-35=f+9 | | 2f-35=f+8/9 | | v=1/3*3.14*(7*x^4)^2*6 | | 3x^2-147+12=0 | | 3j^2+13j+10=0 | | 1/2*-5 | | -8x^2+18x-9=0 | | 3x^2-49+12=0 | | 8g*g*g-2g*g=2g*g-5g*g | | 2a-2=82 | | (-8+5x)-(-2x-9)= | | 0.2x^2-9x+0.2=0 | | 3a-54=a | | 0.2x^2-9x+0.2=o | | a+5+8=15 | | (9x^2-10x)/11x^2 | | 7(x+6)=7(x+10) | | 8(x-6)+5=0 | | 4a-66=a | | w^2+7w-14=0 | | 7x-6=42x-6 | | x-2(5)=-11 | | 3x^2-36+12=0 | | 15(x-2)=10(x+1)-15 | | 2x^2/3x^-25 | | x=-2+2x-5 | | 11y^2+9y-2=0 | | x-2(5)=11 | | 5(x-17)+4=2y+8+3y | | 5d^2-12d-9=0 |